Functional Analysis of BARD1 Missense Variants in Homology‐Directed Repair of DNA Double Strand Breaks. Issue 12 (22nd September 2015) - Lee, Cindy; Banerjee, Tapahsama; Gillespie, Jessica; Ceravolo, Amanda; Parvinsmith, Matthew R.; Starita, Lea M.; Fields, Stanley; Toland, Amanda E.; Parvin, Jeffrey D.
Abstract : Many sequence variants of BARD1, partner protein to BRCA1, have been found in breast cancer patients, but little is known about their clinical significance. Our robust homology‐directed repair assay predicts clinical impact based on the correlation between repair defects and cancer incidence. Mapping these variants to the BARD1 3‐D structures highlights residues crucial to DNA repair and association with BRCA1. ABSTRACT: Genes associated with hereditary breast and ovarian cancer (HBOC) are often sequenced in search of mutations that are predictive of susceptibility to these cancer types, but the sequence results are frequently ambiguous because of the detection of missense substitutions for which the clinical impact is unknown. The BARD1 protein is the heterodimeric partner of BRCA1 and is included on clinical gene panels for testing for susceptibility to HBOC. Like BRCA1, it is required for homology‐directed DNA repair (HDR). We measured the HDR function of 29 BARD1 missense variants, 27 culled from clinical test results and two synthetic variants. Twenty‐three of the assayed variants were functional for HDR; of these, four are known neutral variants. Three variants showed intermediate function, and three others were defective in HDR. When mapped to BARD1 domains, residues crucial for HDR were located in the N‐ and C‐ termini of BARD1. In the BARD1 RING domain, critical residues mapped to the zinc‐coordinating amino acids and to the BRCA1‐BARD1 binding interface, highlighting the importance of interaction between BRCA1 and BARD1 for HDR activity. Based on these results, we propose that the HDR assay is a useful complement to genetic analyses to classify BARD1 variants of unknown clinical significance.